MoSec61β, the beta subunit of Sec61, is involved in fungal development and pathogenicity, plant immunity, and ER-phagy in Magnaporthe oryzae. Issue 1 (31st December 2020) - Wei, Yun-Yun; Liang, Shuang; Zhang, Yun-Ran; Lu, Jian-Ping; Lin, Fu-Cheng; Liu, Xiao-Hong
ABSTRACT: The process of protein translocation into the endoplasmic reticulum (ER) is the initial and decisive step in the biosynthesis of all secretory proteins and many soluble organelle proteins. In this process, the Sec61 complex is the protein-conducting channel for transport. In this study, we identified and characterized the β subunit of the Sec61 complex in Magnaporthe oryzae (MoSec61β). Compared with the wild-type strain Guy11, the Δ Mosec61β mutant exhibited highly branched mycelial morphology, reduced conidiation, high sensitivity to cell wall integrity stress, severely reduced virulence to rice and barley, and restricted biotrophic invasion. The turgor pressure of Δ Mosec61β was notably reduced, which affected the function of appressoria. Moreover, Δ Mosec61β was also sensitive to oxidative stress and exhibited a reduced ability to overcome plant immunity. Further examination demonstrated that MoSec61β affected the normal secretion of the apoplastic effectors Bas4 and Slp1. In addition, Δ Mosec61β upregulated the level of ER-phagy. In conclusion, our results demonstrate the importance of the roles played by MoSec61β in the fungal development and pathogenesis of M. oryzae .